2022
DOI: 10.1039/d2tb01015a
|View full text |Cite
|
Sign up to set email alerts
|

A diselenium-bridged covalent organic framework with pH/GSH/photo-triple-responsiveness for highly controlled drug release toward joint chemo/photothermal/chemodynamic cancer therapy

Abstract: Here, a novel joint chemo/photothermal/chemodynamic therapy was developed using a pH/GSH/photo triple-responsive 2D-covalent organic framework (COFs) drug carriers for passive target treatment of tumor with extraordinarily high efficiency. The well-designed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Due to the pH sensitivity and high affinity of DMTP-TAPB with DOX molecules [ 19 ], COF HPs were investigated for DOX delivery. To load DOX, the nanocarriers were incubated with DOX stock solution at room temperature for 24 h. As summarized in Table 1 , the COF HP had a DOX loading of 46.8%, which was significantly higher than DMSN (15.2%), DMSN@COF (29.1%), and bulk COF (32.1%), and also the highest loading for DOX among the COFs available in the literature [ 16 , 17 , 18 , 19 , 21 ]. The extraordinary loading capacity of COF HPs were mainly attributed to the higher surface area and porosity of the materials ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the pH sensitivity and high affinity of DMTP-TAPB with DOX molecules [ 19 ], COF HPs were investigated for DOX delivery. To load DOX, the nanocarriers were incubated with DOX stock solution at room temperature for 24 h. As summarized in Table 1 , the COF HP had a DOX loading of 46.8%, which was significantly higher than DMSN (15.2%), DMSN@COF (29.1%), and bulk COF (32.1%), and also the highest loading for DOX among the COFs available in the literature [ 16 , 17 , 18 , 19 , 21 ]. The extraordinary loading capacity of COF HPs were mainly attributed to the higher surface area and porosity of the materials ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As for drug delivery applications, it is important to design materials with biocompatible, biodegradable, and stimuli-responsive release properties as well as high loading capacities. To achieve stimuli-responsive release properties, the researchers developed a class of COF materials connected via acid degradable covalent bonds, which makes them promising as intracellular drug delivery vehicles [ 13 , 14 , 15 , 16 , 17 , 18 ]. For instance, Liu et al [ 19 ] reported the 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 2,5-dimethoxyterephthaldehyde (DMTP) connected COF (TAPB-DMTP COF) with cleavable C=N bonds under an acidic environment, which allows for the deconstruction of COF materials inside the subcellular compartments (e.g., endosomes, lysosomes) of tumor cells with an acidic condition of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the typical porous nanomaterials (e.g., silica), the synthesis of MOFs is simpler and more efficient ( Wu et al, 2014 ). Moreover, MOFs can carry metal nanoparticles in for delivering organic materials and drugs with therapeutic purposes ( Dhakshinamoorthy and Garcia, 2012 ), act as a pH/GSH/photo-triple-responsive carrier in developing multimodal chemo/photothermal/chemodynamic therapy ( Lou et al, 2022a ), serve as an artificial enzyme to create a pH sensitive ( Mandal et al, 2022 ) ( Lou et al, 2022b ) ( Xu et al, 2022 ) DDS and as a photoactive dual-cationic covalent MOF to construct a cation/photothermal/NO antibacterial therapy system ( Luo et al, 2022a ) ( Luo et al, 2022b ). Ferey and coworkers first studied the ability of MIL-100(Fe) and MIL-101(Cr) to encapsulate ibuprofen molecules for sustained drug delivery ( Horcajada et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Porphyrin, a common building block of photothermal material, has been extensively studied as an efficient and durable photosensitizer (PS) for antimicrobial therapy. [11] Whereas, the high cost and complex synthesis process limit its applicability. [12] Hence, novel strategies are needed to reduce the cost and finely maintain the antibacterial activity of porphyrin-based agents.…”
Section: Introductionmentioning
confidence: 99%